Gut microbiota: Linking nutrition and perinatal depression - Song, Jia; Zhou, Bi; Kan, Juntao; Liu, Guangya; Zhang, Sheng; Si, Liang; Zhang, Xianping; Yang, Xue; Ma, Junhua; Cheng, Junrui; Liu, Xiaobo; Yang, Yongde (Frontiers in Cellular and Infection Microbiology, 2022)
Perinatal depression is a mood disorder that is reported in women during pregnancy (prenatal) and after childbirth (postnatal). The onset of perinatal depression is associated with changes in reproductive hormones, stress hormones and neurosteroids. These chemical compounds can be modulated by the gut microbiota, which may affect maternal mental health during the perinatal period via the gut-brain-axis. Recent studies suggest that nutritional and dietary interventions (vitamin D, ω-3 fatty acids, iron, and fiber) effectively prevent or mitigate maternal depression and anxiety, but their efficacy is confounded by various factors, including the gut microbiota. Probiotics are efficacious in maintaining microbiota homeostasis, and thus, have the potential to modulate the development of perinatal mood disorders, despite no evidence in human. Therefore, clinical trials are warranted to investigate the role of probiotic supplementation in perinatal depression and behavioral changes. This article reviews the interplay between nutrition, gut microbiota and mood and cognition, and the evidence suggesting that probiotics affect the onset and development of perinatal depression.